Малоресурсний симетричний блоковий шифр «Кипарис» — сутність та основні властивості - Родінко, Марія Юріївна (Kamianets-Podilskyi National Ivan Ohiienko University, 2017)
It is presented a description and the main results of analysis of the main properties of prospective lightweight block cipher «Cypress».